A Review on the Implementation of Construction Safety Management System in ASEAN Development Projects - Fern, Ng Wee; Mohd Masirin, Mohd Idrus (International Journal of Sustainable Construction Engineering and Technology, 2022)
Many countries have focused on emphasizing the importance of construction and health safety management. Countries such as Indonesia, Hong Kong, Malaysia, Vietnam and Cambodia are looking into this issue seriously in order to ensure that the construction industry will always have a positive reputation. The implementation of construction safety management system is very much related to the government policies in construction, the roles of the government agencies, consultants and contractors. This is much more important when many countries are rapidly focusing in developing their facilities and infrastructures towards achieving modern and advance life style community. The rapid emerging economies during this rapid development have created a situation whereby numerous occupational deaths, injuries and illnesses were accounted for among the construction industrial players. Thus, this paper reviews the implementation of construction safety management system in selected countries such as Indonesia, Hong Kong, Malaysia, Vietnam and Cambodia based on projects and experiences by researchers and industrial players from those countries. From the review process, it was found that almost all ASEAN countries are practicing safety and health management system in construction as it is important in all aspect of avoiding possible accidents and fatalities at construction sites. In conclusion, it can be mentioned here that the implementation of construction safety and health management system is an instrument which can be useful not only to avoid accidents and save lives but, it may also enhance the quality of work and outcomes in the construction industry.